The Effectiveness of the Soccer Game to Improve Physical Education, Sports and Health Learning Activities - Andre Rianto, Muhammad Bima (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2024)
Physical and health education aims to change physically, mentally and emotionally through physical activity and fitness. Teachers have a central role in the process of guiding students towards maturity and providing values. However, there are challenges in increasing students' interest in physical education. Internal student factors such as boredom and monotony of monotonous learning methods can influence learning outcomes. Therefore, this research aims to introduce a new approach by integrating the game of header as an interesting learning method in physical education. This research was conducted at MAN 1 Palembang with a focus on class XII students. The aim of the research is to evaluate the effectiveness of the game of header in improving physical learning activities, sports and health. This method is expected to overcome the challenges in motivating students to actively participate in PJOK lessons. With a more interactive approach and involving students in games that support educational goals, it is hoped that student interest and learning outcomes can increase significantly. The results of this analysis provide valuable insight for improving and developing this learning method. Understanding of areas that need improvement, such as aspects of understanding concepts or variations in learning methods.